EWSAT1 Acts in Concert with Exosomes in Osteosarcoma Progression and Tumor‐Induced Angiogenesis: The "Double Stacking Effect". Issue 9 (16th August 2020) - Tao, Shi‐Cong; Huang, Ji‐Yan; Wei, Zhan‐Ying; Li, Zi‐Xiang; Guo, Shang‐Chun
Abstract: The prognosis for osteosarcoma (OS) continues to be unsatisfactory due to tumor recurrence as a result of metastasis and drug resistance. Several studies have shown that Ewing sarcoma associated transcript 1 (EWSAT1) plays an important role in the progression of OS. Exosomes (Exos) act as important carriers in intercellular communication and play an important role in the tumor microenvironment, especially in tumor‐induced angiogenesis. Nonetheless, the specific mechanism via which EWSAT1 and Exos regulate OS progression is unknown, and whether they can be effective therapeutic targets also requires verification. Hence, in this study, it is aimed to investigate the mechanisms of action of EWSAT1 and Exos. EWSAT1 significantly promotes proliferation, migration, colony formation, and survival of OS. EWSAT1 regulates OS‐induced angiogenesis via two mechanisms, called the "double stacking effect, " which is a combination of the increase in sensitivity/reactivity of vascular endothelial cells triggered by Exos‐carrying EWSAT1, and the EWSAT1‐induced increase in angiogenic factor secretion. In vivo experiments further validates the "double stacking effect" and shows that EWSAT1‐KD effectively inhibits tumor growth in OS. The above observations indicate that EWSAT1 can be used as not only a potential diagnostic and prognostic marker, but also as a precise therapeutic target for OS. Abstract : Ewing sarcoma associated transcript 1 (EWSAT1) regulates osteosarcoma (OS)‐induced angiogenesis via two mechanisms, called the "double stacking effect, " which is a combination of the increase in sensitivity/reactivity of vascular endothelial cells triggered by exosomes‐carrying EWSAT1, and the EWSAT1‐induced increase in angiogenic factor secretion from OS cells.